The Effect of Speed Reading on Students’ Reading Comprehension - Dadan Hidayat (Universitas Mathla'ul Anwar Banten, 2019)
This research investigated the effect of speed reading on students’ reading comprehension. The writer used quantitative as the research method and used the quasi experiment as a research design. The writer used experimental class to imply the speed reading method and control group for the other technique in teaching reading. For collecting the data the writer gave the pre – test for experimental and control group, then administrated the treatment for experiment class , finally the researcher administrated the post – test to find out the improvement of speed reading method for the student . Based on the writer interpretation it is concluded that hypothesis is accepted.it is suggested that the teacher should imply the speed reading method in teaching reading because research finding proved that speed reading gave more improvement in reading comprehension that the other technique in teaching reading and the speed reading method was more interesting than conventional method.